Implementation of Project-Based Learning Model in Integrated Science Learning to Improve Science Literacy Aspects - Meo, Katarina; Lawe, Yosefina Uge; Dolo, Fransiskus Xaverius; Kua, Maria Yuliana (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research aims to improve aspects of science literacy by implementing the project-based learning model in integrated science learning for class VIII students at SMP N 1 Soa. Therefore, Classroom Action Research (CAR) was employed in two cycles: planning, implementation, observation, and reflection. The research results show that through the project-based learning model, the percentage in the context aspect in Cycle I was 48.27% with sufficient criteria, while in Cycle II, the percentage was 68.96% in the good category and experienced an increase of 20.69%. The percentage of content aspects in Cycle I was 55.17% with good criteria, while in Cycle II, the percentage was 72.41% in the good category and experienced an increase of 17.24%. The percentage of process aspects in Cycle I was 27.58% with good criteria, while in Cycle II, the percentage was 51.72% in the good category and experienced an increase of 24.14%. Based on the research results, a project-based learning model application helps the students improve science literacy. They become more active and able to work together well in groups by increasing their motivation to learn and their skills in solving problems. With creativity, a project-based learning model application can help in training students to solve problems from various points of view.